Copper Production and Divine Protection. Archaeology. Ideology and Social Complexity on Bronze Age Cyprus - Knapp, A. Bernard (1986)
esp. 96-100: The Late Bronze Age Collapse in the Aegean, Eastern Mediterranean, and the Ancient Near East.